Coverage Algorithm Based on Sensor Residual Energy for Sensor Network - Weifeng Yang; Xiao Liu; Jin Zhang (2010 IEEE Asia-Pacific Services Computing Conference, 2010)
Aiming at the coverage problem, a new coverage algorithm is proposed based on residual energy of sensors in this paper. In the algorithm, it is unnecessary for sensors to know its geographic information. By exchanging some related information with its neighbors, sensors judge its suitable status (active or sleep) according to energy. The algorithm can save sensor energy and extend the time of sensor networks to live. Meanwhile, the network coverage rate can be ensured. Based on theoretical analysis, the algorithm has low complexity and is easy to realize. According to experimental results, the algorithm has good performance.